Mercosur in Brazilian academic production in Social Communication: challenges and prospects - Nubiato Matos, Monica (2017)
This paper studies the postgraduate academic field stricto sensu and those theses and dissertations which aimed Mercosur as its research focus. The techniques used were: data analysis at archives of Alexandre Gusmão Foundation and Research Institute of International Relations (FUNAG/IPRI), bibliographic search y document analysis. We infer that, in twenty-five years of existence of Mercosur, academic production in communications was modest, due to: i) the lack of institutional incentives for research; ii) some indifference towards debates on democratization of communications; and iii) the continuance of traditional diplomacy by governments, which hampers the monitoring of the negotiations and obstructs spaces for social participation.